Increasing Awareness of Young Generation about the Risks of Early Marriage through Socialization in Gunungsari Village, Jatisrono District, Wonogiri Regency: Peningkatan Kesadaran Generasi Muda Tentang Risiko Pernikahan Dini Melalui Kegiatan Sosialisasi di Desa Gunungsari Kecamatan Jatisrono, Kabupaten Wonogiri. - Puri, Nia Esgi; Puyanda, Irvia Resti; Pratama, Bagas Aji; Handaru, Calista Devi (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2025)
Community service activities in Gunungsari Village, Jatisrono District, Wonogiri Regency, aim to increase public knowledge and awareness, especially the younger generation, regarding the risks of early marriage. The socialization involved young men and women in Gunungsari Village, Village Heads, Village Apparatus, and Posyandu Cadres. The method used was active discussions guided by the UNISRI KKN team.The activity began with a presentation of material regarding the definition of early marriage and its prevalence in various rural areas. The results of the socialization showed an increase in public understanding of the negative impacts of early marriage, as well as the importance of prevention through education and community involvement.